Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:Social media marketing strategies and their impact on customer loyaltyMs. Abrar Abdullah AlazzazElectronic Marketing and its Impact on the Corporate Entrepreneurship: A Field Study at Yemeni Private Universities in the Capital Municipality of Sana'aAsst-Prof. Ahmed Qassim Jamal Al-Deen, Mr. Ghaleb Abdullah GhawthThe Impact of the Quality of Tourism Services Provided by Small and Medium Enterprises  on Tourist Satisfaction in North Al Sharqiya Governorate, Sultanate of OmanCo-Prof. Hayel Abd Elmawla Tashtoush, Ms. Yusra Amer Suleiman Al-Maskariyah, Ms. Rahma Salem Abdullah Al-Harthiyah , Ms. Jokha Salem Shannan Al-Zuwaidiyah ,Eng. Asya Yusuf Mohammed Al-MaskariyahThe degree to which strategic leadership is practiced and its relationship to crisis management  in the Public Broadcasting Corporation in the southern governorates SouthernM. Ramzi Moh. Nader Abu HilalThe relationship between managers' emotional intelligence and human resource management effectivenessMs. Munirah A. S. AlGhanimThe Role of Accounting Information Systems in Disclosure of Environmental Costs "A Case Study of Zawiya Oil Refining Company for the Year 2017"Co-Prof. Khaled Al-Bashir Muhammad Ahmad ,Mr. Omar Misbah Al-MazoughiUniversity governance challenges and opportunities in light of the Fourth Industrial RevolutionMs. Fatima A. Algazo, Ms. Zain M. Aldahabi, Dr. Amal Marshed Alanazi, Ms. Rula Yousef Hajjaj
Keywords: Journal of Economic, Administrative and Legal Sciences